Influence of Condom and Contraceptive Pills on Weight Gain among Some Algerian Female Athletes - Zerf, Mohammed (Health Education and Health Promotion (HEHP), 2015)
Aim: This study focuses on the impact of contraceptive methods on weight gain among female athletes. Clinical studies confirm that weight gain is often considered a side effect of hormonal contraceptives and many women think that an association exists; this is while, Sports Medicine and Injuries’ Studies report that this effect is still unclear. This comparative study was designed to dwell on the results of similar studies. Method: Two groups of voluntary female athletes agreed to participate in this study. They were distributed based on the conditions proposed for this study (Group 1 took the oral contraceptive, and Group 2 practised condom) for three cycles of the ovum of the same marital lifestyle. Then they were tested based on the U.S. Federal Government’s Standard Fitness Tests for Women, and their homogeneity was calculated on the basis of age (training and chronology), the typical training program, and social condition. Findings: Based on the research findings: • The proposed techniques prevent pregnancy record in regulating the samples’ menstruation cycle during the experiment. • Practising condom preserves the body weight index composition with a positive physical potential. • Taking oral contraceptive increases the body fat with negative physical potential. • There is a strong positive relationship between the body fat and the level of body fitness in the benefit of condom. Conclusion: Our results are in line with the findings from similar clinical and sport medicine studies, confirming that the use of oral contraceptives increases the percentage of body fat and decreases aerobic fitness among female athletes.
Keywords: Weight gain; Fitness; Conjugal life; Female athletes